Halothane macrophage migration inhibtiion factor test in halothane-associated hepatitis. Issue 4 (April 1977) - Price, C D; Gibbs, A R; Williams, W J
Abstract : As an index of delayed hypersensitivity in vitro halothane macrophage migration inhibition factor tests (halothane-MIF tests) were performed on peripheral blood lymphocytes from five patients with halothane hepatitis. Twenty-two subjects exposed to halothane, but with no evidence of jaundice, five 'healthy' hospital anaesthetists, nine jaundiced subjects without halothane exposure, and 10 healthy subjects with no history of exposure to halothane were also tested. The halothane-MIF test was positive in four of the five patients with halothane-induced hepatitis; the negative result was in a patient on steroid treatment. The test was negative in all other subjects. Our findings suggest that the halothane-MIF test may be of value in the diagnosis of halothane-induced hepatitis and as a screeening procedure for the identification of susceptible subjects.